Online music platforms in Turkey: example of Spotify - Ergün, Ezgi (Istanbul Kultur Univ, Atakoy Campus, Bakirkoy, Istanbul, 34156, Turkey, 2016)
Listening to music have became more accessable with the development of technology, internet and proliferation of smart phones. First and foremost factor of this accessibility is the online music platforms. In this study, one of the online music listening applications Spotify, which comes with free and premium alternatives and accommodates thousands of songs local, foreign and many different categories, is examined in terms of content.
Keywords: Technology; mobile applications; online music; Spotify